How the use of FDG PET is improving the diagnosis of dementia in a reference center in Recife, Brazil - Macêdo, Luisa Couceiro de Albuquerque; Campos, Raphaelly Ribeiro; Nunes, Luiz Eduardo Duarte Borges; Pinheiro, Mariana Gonçalves Maciel; Silva, Alberto Henrique Torres Trindade da; Leão, Maria Regina Vendas Carneiro; Silva, Aldson dos Santos, Júnior; Mourato, Felipe Alves; Brandão, Simone Cristina Soares; Barbosa, Breno José Alencar Pires (Arquivos de Neuro-Psiquiatria, 2025)
Since the advent of 18F-2-fluoro-2-deoxy-D-glucose ([18F]FDG, henceforth, FDG) in the 1970s as a neurochemical tracer, FDG positron emission tomography (PET) has been used for research in dementia and to help diagnose dementing neurodegenerative disorders. However, FDG PET is still unavailable in most centers, especially those in low- and middle-income countries, and there is limited data on biomarkers from patients in diverse populations, such Latin Americans.To analyze the main indications and how the use of FDG PET helped improve the diagnosis of dementia in a specialized center in Recife, one of the largest cities in Northeastern Brazil.We retrospectively analyzed data from 62 individuals under follow-up at our center between 2018 and 2023 who had a clinical diagnosis of dementia or mild cognitive impairment and underwent FDG PET scans.In 21/29 (72.4%) patients, FDG PET helped investigate the types of atypical neurodegenerative dementias; in 14/24 (58.3%), it clarified the clinical question in the investigation of early-onset dementia syndromes; and, in 9 cases, it was performed to differentiate between degenerative and non-degenerative dementias.These numbers may set the foundation for further longitudinal analyses and collaborative studies including participants from Northeastern Brazil.
Keywords: Positron-Emission Tomography; Dementia; Alzheimer Disease